(920) Matrix Inversion (Elimination Methods) عكس المصفوفات (طريقة الحذف) - FOUAD NAKHLA, AFAF; YEHIA YOUSEF, MOHAMED (INP, 2024)
Matrix operations encompass several fundamental concepts in linear algebra. They include matrix algebra, where operations such as addition and multiplication are performed on matrices. The inverse matrix plays a crucial role in solving simultaneous linear equations. These equations can be addressed using methods like Gauss elimination, which simplifies matrices, and Jordan elimination, which focuses on reducing the matrix to a simplified form.